KAJIAN BAURAN PEMASARAN PEMBIAYAAN PENSIUNAN DALAM PENINGKATAN MINAT NASABAH BANK SYARIAH INDONESIA KCP SUMENEP TRUNOJOYO 1 - Holilur Rahman; Mamik Astik Wardasari; Nur Eka Mutmainnah; Kamalina Zulfa; Romsiyeh Romsiyeh; Mubrikatul Mabruroh (Reflektika, 2021)
Pension funds are a funding system in forming accumulated funds. This is needed to maintain continuity of income and work security. The potential for pension funds can support the growth of consumer financing for Indonesian Islamic banks. With this, in order to achieve maximum results it is necessary to have a marketing mix which is one of the marketing strategies to convey information widely, introduce a product and service, stimulate consumers to give and even create personal preferences for the image of a product. Therefore, the marketing mix is considered as one of the most potential strategic elements in marketing products. This study aims to determine the application of the marketing mix for pension financing BSI KCP Sumenep Trunojoyo 1, both in terms of price, low administrative costs and competitive profit sharing, as well as promotions used. The method used in this study is a qualitative method with data collection techniques which include observation, interviews, and documentation. Implications of the marketing mix in increasing customer interest in retirement financing Bank Syariah Indonesia KCP Sumenep Trunojoyo 1 implements the 4P marketing mix strategy (product, price, place, promotion). The marketing strategy in dealing with competition for retirement financing products at Bank Syariah Indonesia KCP Sumenep Trunojoyo 1 uses a special attack strategy, namely direct visits to the residences of prospective customers and permanent customers